The Influence of Organizational Culture, Job Training and Motivation on Employee Performance in Credit Union Employees in Pontianak City - Alberd Alberd (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study was conducted to find out the extent to which organizational culture, job training, and motivation affect employee performance at Credit Union in Pontianak City. The research data was obtained through the distribution of questionnaires and processed using the SPSS version 25 (Statistical Program for Social Science) program. Data analysis was carried out using the Likert scale, a classical assumption test that included normality, linearity, and heteroscedasticity tests, and continued with multiple linear regression tests, determination coefficients, and hypothesis tests (F test and t test). The results of the validity test showed that all instruments in the independent variable (X) and the dependent variable (Y) were declared valid. Furthermore, the results of the t-test show that organizational culture (X1) has a positive and significant influence on employee performance. Meanwhile, job training (X2) actually shows a negative influence on performance. The motivation (X3) has been proven to have a positive effect on employee performance at Credit Union in Pontianak City.